Pengaruh Media Pop-Up Book Digital “Sang Garuda” Pada Pembelajaran Pendidikan Pancasila Terhadap Motivasi Belajar Siswa - khoir, nafi; Ardita Juliyanti; Ika Dian Rahmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
The era of globalization and advances in digital technology has brought considerable challenges to the world of education, one of which is the declining learning motivation among students in Pancasila Education subject, largely attributed to teaching approaches that tend to be repetitive and lack variation. This study aims to examine the effect of implementing the